2013
DOI: 10.1137/120888132
|View full text |Cite
|
Sign up to set email alerts
|

Stokes Complexes and the Construction of Stable Finite Elements with Pointwise Mass Conservation

Abstract: Abstract. Two families of conforming finite elements for the two-dimensional Stokes problem are developed, guided by two discrete smoothed de Rham complexes, which we coin "Stokes complexes." We show that the finite element pairs are inf-sup stable and also provide pointwise mass conservation on very general triangular meshes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 24 publications
1
131
0
1
Order By: Relevance
“…Here, the authors showed that the pair P k − P dc k−1 is stable in two dimensions on simplicial triangulations provided the polynomial degree satisfies k ≥ 4 and if the triangulation does not contain singular vertices. These results have since been expanded in [13,16]. Similar to the simplicial case, the construction of Stokes pairs yielding divergence-free approximations on Cartesian meshes is mostly limited to the two dimensional case [4,17,26].…”
Section: 4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the authors showed that the pair P k − P dc k−1 is stable in two dimensions on simplicial triangulations provided the polynomial degree satisfies k ≥ 4 and if the triangulation does not contain singular vertices. These results have since been expanded in [13,16]. Similar to the simplicial case, the construction of Stokes pairs yielding divergence-free approximations on Cartesian meshes is mostly limited to the two dimensional case [4,17,26].…”
Section: 4)mentioning
confidence: 99%
“…As pointed out in [13], imposing boundary conditions of finite element spaces while preserving the surjectivity of the divergence is a non-trivial issue. For example, if v is a globally continuous function on Ω and vanishes on ∂Ω, then the derivatives of v vanish at corners (n = 2) and edges (n = 3) of ∂Ω.…”
Section: Global Finite Element Spaces With Imposed Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the work of, e.g., Arnold, Qin, Zhang, Neilan, Guzman, and Falk [1][2][3][4][5], several choices such as Scott-Vogelius elements are now available that are LBB stable (sometimes requiring a mesh condition), are sufficiently low degree so as to be practical, provide ∥∇ · u h ∥ = 0 for the discrete velocity solution, and also deliver optimal asymptotic accuracy of the velocity in the energy norm. We refer to such mixed finite elements as divergence-free elements.…”
Section: Introductionmentioning
confidence: 99%
“…There are several other such divergence-free finite elements, cf. [2,14,16,17,19,20,[29][30][31]33].…”
mentioning
confidence: 99%